2019
DOI: 10.3389/fnins.2019.01093
|View full text |Cite
|
Sign up to set email alerts
|

Auditory, Cognitive, and Linguistic Factors Predict Speech Recognition in Adverse Listening Conditions for Children With Hearing Loss

Abstract: Objectives: Children with hearing loss listen and learn in environments with noise and reverberation, but perform more poorly in noise and reverberation than children with normal hearing. Even with amplification, individual differences in speech recognition are observed among children with hearing loss. Few studies have examined the factors that support speech understanding in noise and reverberation for this population. This study applied the theoretical framework of the Ease of Language Understanding (ELU) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 51 publications
6
85
1
1
Order By: Relevance
“…In the context of children with mild-to-severe hearing loss, Stiles and colleagues ( Stiles et al, 2012 ) found a significant relationship between digit span and vocabulary size in both CNH and CHL. More recently, McCreery et al (2019) found that, in addition to language and auditory factors, phonological working memory ability significantly predicted speech recognition in CHL, which echoed the pattern of results found in an earlier study in children with normal hearing from the same authors ( McCreery et al, 2017 ). Importantly, neither of these studies showed that there were significant differences in working memory ability between CNH and CHL.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…In the context of children with mild-to-severe hearing loss, Stiles and colleagues ( Stiles et al, 2012 ) found a significant relationship between digit span and vocabulary size in both CNH and CHL. More recently, McCreery et al (2019) found that, in addition to language and auditory factors, phonological working memory ability significantly predicted speech recognition in CHL, which echoed the pattern of results found in an earlier study in children with normal hearing from the same authors ( McCreery et al, 2017 ). Importantly, neither of these studies showed that there were significant differences in working memory ability between CNH and CHL.…”
Section: Introductionsupporting
confidence: 77%
“…Despite the growing literature suggesting that working memory capacity is significantly linked to language function in those with and without hearing loss ( McCreery et al, 2017 , McCreery et al, 2019 , Stiles et al, 2012 ), there has been no investigation of the neural dynamics underlying these relationships to date. To this end, this study used MEG during a well-established verbal working memory task and a battery of neuropsychological tests to determine the impact of hearing loss on neural oscillatory dynamics that underlie working memory encoding and maintenance processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classroom noise is known to cause distraction and annoyance in children, but its primary effect is a reduction in speech intelligibility (for reviews, see Shield and Dockrell, 2003;Klatte et al, 2013), with a consequently negative impact on academic achievement (Shield and Dockrell, 2008). In typically developing children, the ability to cope with speech in noise (SiN) has been linked to individual differences in cognitive and language abilities (Nelson et al, 2005;Strait et al, 2012;MacCutcheon et al, 2019), age (Corbin et al, 2016), gender (Prodi et al, 2019), and supra-threshold auditory processing abilities (Lorenzi et al, 2000), as well as environmental factors, including reverberation and the spatial, spectral and temporal characteristics of the background noise (MacCutcheon et al, 2018(MacCutcheon et al, , 2019McCreery et al, 2019).…”
Section: Introductionmentioning
confidence: 99%